1995
DOI: 10.1007/bf01781199
|View full text |Cite
|
Sign up to set email alerts
|

Serumantikörper gegen die Komponenten der Diphtherie-Tetanus-Pertussis-Vakzine bei polnischen Kindern in Beziehung zum Impfstatus

Abstract: In Poland vaccination against diphtheria, tetanus and pertussis (DTP) is recommended from 2-3 months of age. Three doses at approximately 6-week intervals are given. A booster dose of DTP is given at 19-24 months and boosters of DT at 6 and 14 years. In this study serum samples were obtained from 166 Polish children aged 2 weeks to 14 years. Vaccination status was verified from the children's Health Books. Antibodies were determined against pertussis toxin, filamentous hemagglutinin (FHA), pertactin, tetanus t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
1
0
0
Order By: Relevance
“…While the reason for this difference is poorly understood, it is most likely due to the quantity of each one of these antigens present in the cellular vaccine, in agreement with findings reported by other authors who demonstrated wide variations in antibody levels induced by diverse cellular vaccines [54,55]. Regarding the persistence of antibodies against these two antigens, results obtained in the adult group show that anti-PT levels decline over time, whereas those of anti-FHA remain high, similar to findings from other parts of the world [56,57]. Presumably, exposure to Bordetella parapertussis, which also expresses FHA, or to cross-reacting antigens of other bacteria, may explain the persistence of raised anti-FHA levels in adults.…”
Section: Discussionsupporting
confidence: 93%
“…While the reason for this difference is poorly understood, it is most likely due to the quantity of each one of these antigens present in the cellular vaccine, in agreement with findings reported by other authors who demonstrated wide variations in antibody levels induced by diverse cellular vaccines [54,55]. Regarding the persistence of antibodies against these two antigens, results obtained in the adult group show that anti-PT levels decline over time, whereas those of anti-FHA remain high, similar to findings from other parts of the world [56,57]. Presumably, exposure to Bordetella parapertussis, which also expresses FHA, or to cross-reacting antigens of other bacteria, may explain the persistence of raised anti-FHA levels in adults.…”
Section: Discussionsupporting
confidence: 93%